PENERAPAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENCEMARAN NAMA BAIK DALAM HUKUM PIDANA ISLAM - Noercholis Rafid A (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2022)
This research discusses the application of restorative justice to criminal defamation in Islamic criminal law. This research is a literature research that examines literature related to problems that are studied using normative theological approaches and juridical approaches. This study aims to elaborate and compare the application of restorative justice to criminal defamation in Islamic criminal law and national criminal law. The implication of this study is that the application of restorative justice to defamation crimes in Islamic criminal law is resolved by mediation (outside the court) first and then through the court channel.